Technological advances and challenges in constructing complex gut organoid systems - Zheng, Longjin; Zhan, Yang; Wang, Chenxuan; Fan, Qigui; Sun, Denglong; Li, Yingmeng; Xiong, Yanxia (Frontiers in Cell and Developmental Biology, 2024)
Recent advancements in organoid technology have heralded a transformative era in biomedical research, characterized by the emergence of gut organoids that replicate the structural and functional complexity of the human intestines. These stem cell-derived structures provide a dynamic platform for investigating intestinal physiology, disease pathogenesis, and therapeutic interventions. This model outperforms traditional two-dimensional cell cultures in replicating cell interactions and tissue dynamics. Gut organoids represent a significant leap towards personalized medicine. They provide a predictive model for human drug responses, thereby minimizing reliance on animal models and paving the path for more ethical and relevant research approaches. However, the transition from basic organoid models to more sophisticated, biomimetic systems that encapsulate the gut's multifaceted environment-including its interactions with microbial communities, immune cells, and neural networks-presents significant scientific challenges. This review concentrates on recent technological strides in overcoming these barriers, emphasizing innovative engineering approaches for integrating diverse cell types to replicate the gut's immune and neural components. It also explores the application of advanced fabrication techniques, such as 3D bioprinting and microfluidics, to construct organoids that more accurately replicate human tissue architecture. They provide insights into the intricate workings of the human gut, fostering the development of targeted, effective treatments. These advancements hold promise in revolutionizing disease modeling and drug discovery. Future research directions aim at refining these models further, making them more accessible and scalable for wider applications in scientific inquiry and clinical practice, thus heralding a new era of personalized and predictive medicine.